Quality of Work-Life for Job Satisfaction in Nepalese Commercial Banks - Adhikari, Pitri Raj (Management Dynamics, 2019)
This paper is concerned with the examination of the impact of quality of work life for job satisfaction in Nepalese commercial banks. To achieve the purpose of the study, structured questionnaire is prepared and collected from 225 respondents. Descriptive and casual comparative research design have been used in this study. The multiple regression model has been used to test the relationship. The results show that working environment, work life balance, compensation and reward, training and development, and job design are positively related to job satisfaction. The regression result shows that the beta coefficients for all variables are positive and significant with job satisfaction.